Penelitian Tindakan Kelas (PTK) Inovatif melalui Integrasi Teknologi dan Media dalam Pembelajaran Abad ke-21 - Isnur, Sandy Jayusman; Alrasi, Fitri (TSAQOFAH, 2026)
This study aimed to examine the concept of Classroom Action Research (CAR), its research design, variables, and data collection techniques in the context of twenty-first-century learning through the integration of technology and instructional media. A qualitative approach was employed using library research by reviewing various literature sources, including reference books, national and international journal articles, and relevant educational policy documents published in the last ten years. The findings show that CAR is a reflective and systematic approach that enables teachers to improve the quality of learning processes and outcomes through iterative cycles of planning, action, observation, and reflection. Innovative CAR in twenty-first-century learning emphasizes technology integration, collaborative learning, project-based learning, and other creative strategies aligned with twenty-first-century skills. In addition, the use of diverse data collection techniques (such as observation, tests, interviews, reflective journals, and documentation) strengthens triangulation and enhances the validity of research findings. Overall, CAR functions not only as a means of solving classroom learning problems but also as an instrument for developing teacher professionalism in designing active, meaningful, learner-centered, and digitally adaptive instruction.